PRODUCTION OF GRADIENT MATERIALS BY MEANS OF SVS IN THE FIELD OF MASS POWERS - V. V. Klubovich; M. M. Kulak; V. V. Rubanik; V. V. Samolyotov (Литьë и металлургия)
Influence of centrifugal overload on distribution of refractory strengthening particles in volume of melt is studied, structures of initial burden and methods of centrifugal casting of samples from materials on the basis of iron with high wear resistance and gradient distribution of particles of carbides and borides are developed.